1967
DOI: 10.1099/00221287-47-3-405
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Physico-Chemical Analysis of Fractions from the Culture Supernatant of Escherichia coli O78K80: Free Endotoxin and a Non-Toxic Fraction

Abstract: SUMMARYThe extracellular production of ' free endotoxin ' from Escherichia coli serotype 078K80 is discussed. Isolation of purified toxic and non-toxic fractions from crude extracellular material and the physico-chemical properties of these fractions are described. Purified free endotoxin possessed similar properties to endotoxins extracted from the bacteria by conventional procedures ; a purified non-toxic extracellular fraction corresponded to the so-called ' native hapten '. When dissolved in buffers contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

1968
1968
1986
1986

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…In addition to free endotoxin, non-toxic material of lower molecular weight was present in culture fluids of Escherichia coli serotype 078 K 80 (Marsh & Crutchley, 1967). This substance was similar to native hapten described by Anacker et al (1964) or as it is now called, native protoplasmic polysaccharide (Rudbach et al 1967).…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…In addition to free endotoxin, non-toxic material of lower molecular weight was present in culture fluids of Escherichia coli serotype 078 K 80 (Marsh & Crutchley, 1967). This substance was similar to native hapten described by Anacker et al (1964) or as it is now called, native protoplasmic polysaccharide (Rudbach et al 1967).…”
Section: Resultsmentioning
confidence: 71%
“…The body temperatures remained low for as long as 12 hr, whereas the diarrhoea lasted for only 2 hr. These findings suggested that culture fluids from aerated cultures contained endotoxin which we propose to call 'free endotoxin', to distinguish it from material extracted from whole bacteria by chemical methods (Crutchley et al 1967).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations